Synchronous Bilateral Testicular Tumors with Different Histopathology - Ioannis Anastasiou; Dimitrios Deligiannis; Ioannis Katafigiotis; Ioannis Skarmoutsos; Georgios Karaolanis; Viktoria-Varvara Palla; Afrodite Nonni; Dionysios Mitropoulos; Constantinos A. Constantinides (Case Reports in Urology)
A 40-year-old male presented to our outpatient department with the chief complaint of a painless mass on his right testis with gradual size increase over the past two months. Physical examination and ultrasound revealed a firm and nontender mass both on the right and on the left testis. The only elevated biomarker was b-hcG (24,7 mIU/mL) and computer tomography (CT) did not reveal any pathology. Bilateral high orchiectomies were performed, without previous frozen storage of the sperm. Histology proved typical seminoma of the left testis and embryonal carcinoma of the right testis. He received two cycles of adjuvant combination chemotherapy with bleomycin, etoposide, and cisplatin. Six months after the operation no residual tumor or recurrence was observed.